A Review of Indications and Guidelines of Chronic Total Occlusion Revascularization - Kotev, Spas; Sami, Farhad; Malangu, Boniface (International Journal of Angiology, 2025)
Chronic total occlusion (CTO), affecting 18 to 30% of coronary artery disease patients undergoing angiography, is linked to refractory angina, reduced left ventricular function, and increased arrhythmia risk. This article synthesizes indications, evidence, and guidelines for CTO revascularization, focusing on percutaneous coronary intervention (PCI). CTO PCI achieves over 85% success rates in expert hands, with randomized controlled trials showing improved symptom relief and quality of life, though mortality or ventricular function benefits remain unproven. The 2021 ACC/AHA/SCAI and 2018 ESC/EACTS guidelines recommend CTO PCI for refractory angina, emphasizing operator expertise and shared decision-making. Controversies persist regarding prognostic benefits and patient selection. Ongoing trials aim to clarify these issues. This review equips clinicians with a framework to navigate CTO management, balancing evidence and patient-centered care.
Keywords: coronary artery; coronary intervention; chronic total occlusion; guidelines; indications; coronary angiography